2018
DOI: 10.1002/cpt.1178
|View full text |Cite
|
Sign up to set email alerts
|

Safety Threshold Considerations for Sunscreen Systemic Exposure: A Simulation Study

Abstract: Sunscreens are regulated as over-the-counter drugs in the United States. Some sunscreen ingredients are absorbed into the systemic circulation, which raises concerns about the safety of these drugs. There is limited information on the systemic exposure for most sunscreen ingredients. This report estimates the systemic absorption of two sunscreen active ingredients, oxybenzone and enzacamene, by developing a pharmacokinetic model from published sunscreen absorption data and compares the results with safety thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[1][2][3][4] For some individuals, sunscreen products may be applied in substantial amounts multiple times every day over the course of a lifetime as both primary sunscreen products, starting from an age of 6 months, and as ingredients in cosmetic products. 5 Application to the skin can result in multiple grams of sunscreen being applied in a day, even with modest use. 5 Although OTC sunscreen products are widely used, little is known about systemic exposure for most active ingredients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] For some individuals, sunscreen products may be applied in substantial amounts multiple times every day over the course of a lifetime as both primary sunscreen products, starting from an age of 6 months, and as ingredients in cosmetic products. 5 Application to the skin can result in multiple grams of sunscreen being applied in a day, even with modest use. 5 Although OTC sunscreen products are widely used, little is known about systemic exposure for most active ingredients.…”
mentioning
confidence: 99%
“…5 Application to the skin can result in multiple grams of sunscreen being applied in a day, even with modest use. 5 Although OTC sunscreen products are widely used, little is known about systemic exposure for most active ingredients. 6 Understanding the extent of systemic exposure of these products is important, as even a low percentage of systemic absorption (eg, 0.1%) could represent a significant systemic exposure (eg, milligrams of ingredient being systemically absorbed per day).…”
mentioning
confidence: 99%
“…In particular, 5-hydroxylation seems catalyzed by P450 3A2, 1A1, 2B1, 2C6 and 2D1, while 4-desmethylation seems catalyzed by P450 2C6 and isoform CYP1A1 [12,14]. Metabolites of benzophenone-3 show disrupting effects toward other nuclear receptors, potent estrogenic and anti-androgenic activities, and are potentially prone to DDIs [1,14]. Structural requirements for activity were investigated in a series of 14 benzophenone-3 derivatives.…”
Section: Biotransformation Of Sunscreen Ingredientsmentioning
confidence: 99%
“…Their use is considered completely safe, so they are classified among the over-the-counter products, and are applied with no limitation, on more or less extensive body surface, multiple times every day. Recent studies [1,2] have shown that active sunscreen components are adsorbed into systemic circulation and can be detected in significant amounts in vital organs; details on pharmacokinetic of these compounds are cumulating, highlighting the risk of toxicity and drug-drug interactions (DDIs) with a wide range of commonly utilized drugs.…”
Section: Introductionmentioning
confidence: 99%
“…There should be discrimination in the use of topical skin care products, particularly sunscreens, most of which contain the ultraviolet chemical filter oxybenzone (benzophenone-3; BP-3). BP-3 is an established EDC that shows remarkable systemic absorption [228], and which was recently detected in 97% of the population in a Center of Disease Control study [229]. Mineral-based sunscreens, containing zinc oxide or titanium dioxide as active ingredients, are now recommended over others.…”
mentioning
confidence: 99%